Comparison of the success of medial patellofemoral ligament reconstruction techniques - Almeida, Peter Richard (University of the Witwatersrand, Johannesburg, 2023)
Introduction: Recurrent lateral patella instability is multifactorial, with the current emphasis of treatment being to restore the medial stabilising structures to prevent further dislocations and complications. Many treatment options have been documented and Medial Patella Femoral Ligament (MPFL) reconstruction has become the most common surgical method, yet there is no gold standard technique reported for MPFL reconstruction. The aim of this study was to compare the success of different MPFL reconstruction techniques especially double bundle technique (DBT) versus single bundle technique (SBT). Methods: A retrospective review of the records of patients who had MPFL reconstructions performed over a 10-year period at a single orthopaedic practice was conducted. Patient demographic details, including Body Mass Index (BMI) and the surgical technique used, including DBT or SBT, and graft choice were recorded. Outcome measures included re-dislocation rate, Kujala knee questionnaire, Tegner activity scale and visual analogue scale (VAS) assessing satisfaction. Results: One hundred and thirty-three patients underwent MPFL reconstruction, 17 patients were excluded. Thirty-one patients were lost to follow up. A total of 85 (73.28%) patients were assessed. Mean age was 23.9 years and 63.53% (n = 54) were female. The average follow up was 80.6 months, with 3.5% (n = 3) patients that re-dislocated requiring revision surgery. The mean Kujala knee score was 85, the mean Tegner activity scale was 5.6 and the mean VAS satisfaction score was 9. DBT reconstructions accounted for 45.9% (n = 39) of procedures, while 54.1% (n = 46) of patients underwent SBT reconstruction. Of the SBT group 19.57% (n = 9) utilised allograft. No statistical significance between dislocation rate (p = 0.810), Tegner activity score (p = 0.155), Kujala knee score (p = 0.265) or patient VAS satisfaction scores (p = 0.989) between the DBT and SBT groups was found. No significant difference was found in the outcomes between allograft and autograft. Sixty-nine percent of patients completed rehabilitation, with significantly higher Kujala knee scores noted in those patients (86.8 ± 10.586) compared to than those who did not complete rehabilitation (81.04 ± 14.05) (p = 0.040). Conclusion: The use of either SBT or DBT in MPFL reconstruction, as well as the use of allograft or autograft, resulted in similar favourable outcomes. This follows the trend reported in previous literature. Other factors such as rehabilitation and articular damage noted at the time of surgery may influence outcomes more. Higher-powered prospective studies are required to better determine which techniques may be superior.
This research report has been written for submission as part of the requirement for the degree of Master of Medicine, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Medial patellofemoral reconstruction; Patella instability; Double bundle; Single bundle; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education